The impact of IFRS-based accounting standards on earnings management: evidence from Malaysia - Fourati, Yosra Makni; Ghorbel, Rania Chakroun (International Journal of Accounting and Economics Studies, 2016)
This study aims to examine the consequences of International Financial Reporting Standards (IFRS) convergence in an emerging market. More specifically, we investigate whether the adoption of the new set of accounting standards in Malaysia is associated with lower earnings management. Using a sample of 3,340 firm-year observations across three reporting periods with different levels of IFRS adoption, we provide evidence that IFRS convergence improves earning quality. In particular, we find a significant decrease in the absolute value of discretionary acccruals in the partial IFRS-convergence period (2007-2011), whereas this effect is restrictive after the complete IFRS- implementation.